Technopreneurship Training to Improve the Competitiveness of Local Community Products - Subhan Subhan; Muhammad Fadhil; Raka Aldi Pranoto; Ari Susanto (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to describe technopreneurship strategies as an approach to empower small and medium enterprises (SMEs) in Padanglampe Village to increase the competitiveness of local products. The primary focus of the study is how the use of technology can strengthen the capacity for innovation, production, and digital-based marketing for the PKK women's group as program partners. Research Design and Methodology: The activities were carried out through the Community Service Program (PkM) using participatory training methods. The implementation included providing materials, demonstrations, hands-on practice, and mentoring on entrepreneurship, product innovation, digital marketing, and simple business management. Findings and Discussion: Technopreneurship training has been proven to improve participants' knowledge, skills, and digital literacy. PKK members demonstrated improved abilities in product design, marketing via online platforms, and optimizing technology in the production process. This activity also strengthened entrepreneurial motivation and opened up more competitive business opportunities. Implications: This program has practical implications for women's empowerment and village economic development, grounded in local potential. Technopreneurship training can serve as a sustainable model for village governments, academics, and MSME communities to strengthen business capacity, expand market access, and enhance the competitiveness of local products.